PENENTUAN JUMLAH PRODUKSI UD MEGA SAPUTRA MENGGUNAKAN FUZZY TSUKAMOTO - Ucik Airtanti; Kustanto Kustanto; Hendro Wijayanto (STMIK Sinar Nusantara, 2018)
The breaking of bread production at UD Mega Saputra always rely on estimation only. Where with the many deficiencies found that resulted in losses for the company. Based on the inventory data and the number of requests, then designed a system of determining the amount of production using Tsukamoto method. In this system of production determination, there are three variables that are modeled, namely: demand, supply, and production. Steps to make Determination of Production Amount UD Mega Saputra Using Fuzzy Tsukamoto include designing the concept, collecting data, preparation of hardware and software, making modeling diagram, making application, testing, repairing, and completion. One example calculation using Tsukamoto method with type of mocca bread produce70 bread, banana bread produce as many as 244 and donat produce an amount of 291 of bread per week.Keywords: fuzzy Tsukamoto, production amount, bread production, fuzzy